Cape Verde in West Africa region: towards a new paradigm for regional integration - Madeira, João Paulo (2016)
The West African region has immeasurable natural resources and a market of more than 300 million consumers, contributing directly to the dynamics of the global economy. This article aims to identify the importance of this region in the development of Cape Verde, an economically dependent country that has given primacy to its foreign policy to bet on political and economic diplomacy. This investigation was a literature review, complemented through an interpretative analysis, in which the results obtained may allow to consider that the archipelago of Cape Verde needs to delineate a new paradigm of regional integration, vying for the West African geo-economics’ space and using as a platform to provide services to other ECOWAS countries, so that the gains may also revert to the strengthening of cooperation with the African continent.